Analysis of Mosques Financial Management Practices in Gowa Regency, Indonesia - Suarni, Agusdiwana; Wahyuni, Sri; Nurlina, Nurlina (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2023)
This study aims to determine how the Practice of Mosque Financial Management in Bajeng District, Gowa Regency. This study interviewed 3 mosque administrators, namely: Mosque Chairman, Mosque Secretary and Mosque treasurer. The type of research used in this research is descriptive qualitative research. Data collection techniques are obtained through observation, interviews and documentation. The data obtained are secondary data and primary data. The finding of this research which are (1) budget planning, the mosque in Limbung Village is only the Limbung Grand Mosque which does budget planning regularly and others only do plan when there are activities or mosque construction and some have never even done a budget plan. (2) fund management, the source of mosque income is dominated by Friday infaq and other income such as donors and in the month of Ramadan there is also Amalia Ramadhan. Mosque expenditures are mostly used for mosque operations as well as the construction and physical maintenance of the mosque. (3) internal control, all mosques have used evidence such as notes / receipts for recording and reporting their finances, although financial reports still use simple financial reports and are made manually but mosque administrators are transparent by submitting financial reports every Friday before Friday prayers. Budget evaluation is still a lot of mosques that have never done it and only done by a few mosques in Limbung Village and even then, it is done when there are big activities, while for audits, quite a lot of mosques in Limbung Village have done it where financial reports made by the treasurer will be checked by the head of the mosque management.